Ethosomal Systems As a Novel Non-Invasive Vesicular Platform Drug Delivery - Dakhil, Ibtihal Abdulkadhim; Noori, Mustafa M.; Abbas, Ali Khidher; Khudhair, Aqeel Abdulridha (Journal of Pharmacology and Drug Development, 2026)
ObjectiveExamine how transdermal drug delivery systems can yield advantages over conventional methods, especially in terms of maximizing efficacy while reducing toxicity and bypassing hepatic metabolism. The study also aims to review ethosomal systems as a novel nanocarrier for enhanced transdermal drug delivery.MethodsA comprehensive review of transdermal drug delivery systems with an accent on ethosomes. Three types of ethosomal systems were studied based on their composition, which are transethosomes, binary ethosomes, and classical ethosomes. These methods were explored to determine how the differences in preparation techniques and formulation methods influenced system properties, including vesicle size, zeta potential, drug entrapment efficiency, skin penetration, and stability.ResultsEthosomes are emerging as potent transdermal drug carriers.They can encompass drugs with a broad diversity of physicochemical properties, and due to their high ethanol levels, ethanol has been used to increase the penetration of the drug molecules by disrupting the lipid structure of the stratum corneum.(Due to the deeper skin layers,it may include the subcutaneous layer,but the target for transdermal drug delivery is that the drug is systemically absorbed before reaching this layer).  Transethosomes and binary ethosomes exhibited better flexibility and permeation than conventional ethosomes ConclusionsEthosomal systems have better drug penetration, lower toxicity, and higher therapeutic efficacy.This makes them a promising new way to give drugs through the skin. The performance of formulation ingredients and preparation methods has a big effect on how well they work. More research and improvements to these systems could make them more useful in medicine and pharmacology.